PENGARUH KONFLIK PEKERJAAN-KELUARGA (WORK FAMILY CONFLICT) DAN BEBAN KERJA TERHADAP STRES KERJA DAN KINERJA BENDAHARA WANITA DINAS PEKERJAAN UMUM KABUPATEN/ KOTA SE PULAU LOMBOK) - SILVIA ARIANI (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2017)
The aim of this research is to analysis the influence of work family conflict toward work stress, workload toward work stress, work family conflict toward work performance, and workload toward work performance and work stress toward work performance in Woman Treasurer at PU Agency of Lombok Regency/City in all around Lombok Island. The method of collecting data that being  used is census method. The population in this research is all of the woman treasurer in PU Agency of Lombok Regency/City in all around Lombok Island environment. The amount of this population are 37 people, all of these people are being respondents. The analysis tools that being used is PLS (Partial Least Square). The technique of collecting data that being used are questionnaire, interview, and documentation, the tool of collecting data that being used is questionnaire. The result of this research showing that work family conflict and workload has positive and significant influence toward work stress, work family conflict and workload has negative and significant influence toward work performance and work stress has negative and significant influence toward work performance in Woman Treasurer at PU Agency of Regency/City in all around Lombok Island.Keyword          :Work Family Conflict, work stress, workload, and work performanceThe aim of this research is to analysis the influence of work family conflict toward work stress, workload toward work stress, work family conflict toward work performance, and workload toward work performance and work stress toward work performance in Woman Treasurer at PU Agency of Lombok Regency/City in all around Lombok Island. The method of collecting data that being  used is census method. The population in this research is all of the woman treasurer in PU Agency of Lombok Regency/City in all around Lombok Island environment. The amount of this population are 37 people, all of these people are being respondents. The analysis tools that being used is PLS (Partial Least Square). The technique of collecting data that being used are questionnaire, interview, and documentation, the tool of collecting data that being used is questionnaire. The result of this research showing that work family conflict and workload has positive and significant influence toward work stress, work family conflict and workload has negative and significant influence toward work performance and work stress has negative and significant influence toward work performance in Woman Treasurer at PU Agency of Regency/City in all around Lombok Island.Keyword          :Work Family Conflict, work stress, workload, and work performance[1][1] Mahasiswa Program Magister Manajemen Pascasarjana Universitas Mataran2 Dosen Pembimbing Utama, Dosen Program Magister Manajemen Pascasarjana Universitas Mataram3 Dosen Pembimbing Pendamping, Dosen Program Magister Manajemen Pascasarjana Universitas Mataram